A study on unhealthy cervix and its risk factors among currently married women of reproductive age group attending an urban health centre of Kolkata - Dasgupta, Aparajita; Sinha, Rabindra Nath; Paul, Bobby; Bandhopadhay, Lina; Banerjee, Rajarshi; Suman, Sweta (International Journal Of Community Medicine And Public Health, 2019)
Background: Cancer of cervix is the third most common cancer in women in India accounting for 21.7% of cancer deaths among women. Unhealthy cervix, characterized by presence of any abnormal growth, ulcer, or vasculature, is a clinically detectable early stage in the life history of cervical cancer. Very few studies have been conducted to determine risk factors of unhealthy cervix. Methods: A clinic-based cross-sectional study was conducted among currently married women of reproductive age group attending Urban Health Unit and Training Centre, Chetla, Kolkata. A total of 189 women attending the clinic was selected using systematic random sampling method was who were interviewed and examined using pre-designed pre-tested schedule. Analysis was done using (SPSS version 16). Results: Among 189 women, 45.5% were diagnosed with unhealthy cervix. Hierarchical logistic regression showed that educational status, PCI, frequency of cleaning external genitalia and extramarital relationship of the spouse were significantly associated with unhealthy cervical condition. Conclusions: Most of the risk factors of unhealthy cervix are behavioral and modifiable. Health education and behaviour change communication of women of reproductive age group would help in reducing their morbidity as well as mortality from cervix related conditions that includes cervical cancer.